Factors associated with the maintenance and interruption of exclusive breastfeeding: a literature review (Research, Society and Development, 2024)
Breastfeeding is ideal for meeting food and nutritional needs during the first six months of life, bringing many benefits not only to the newborn, but also to the mother and family, in addition to being practical and economical. The recommendation for good breastfeeding practices is up to six months of age or up to two years. The objective was to identify, according to the literature, the factors associated with the maintenance and/or interruption of exclusive breastfeeding in the first six months of life in Brazil. This is an integrative literature review. Studies were collected in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS), SCIELO and BDENF, in addition to the PUBMED and SCOPUS databases, totaling 10 selected articles. Based on the results, adherence to breastfeeding or early weaning is often associated with the assistance provided by professionals during prenatal consultations. There are several factors contributing to the interruption, such as low maternal education, longer stay in the NICU, lack of information and encouragement on the part of professionals and the maternal perception of not having a sufficient amount of milk. Previous experience with breastfeeding proved to be an important factor for maintaining exclusive breastfeeding. In addition, it brings the role of the family and/or the mother's support network for maintenance, which was contrary to some findings in the literature, emphasizing that this reality is not homogeneous.